Advantage of Diurnal Amplitude Variation (DAV) of Brightness Temperature in Revealing the Land‐Atmosphere Interaction Over the Region of Frozen and Thawed Soil in the Northern Hemisphere During the Cold Wave Movements - Yin Hu; Shaoning Lv; Yuanyuan Guo; Haihua Bai; Altanchimeg Dorjsuren; Yijun Zhang; Jun Wen (Geophysical Research Letters, 2025)
Abstract During cold wave movements, land‐atmosphere interaction functions as a “switch” mechanism, regulating energy and moisture exchange. However, existing methods have limitations in capturing this process. The dielectric contrast between frozen and thawed soil induces diurnal amplitude variation (DAV) in brightness temperature at L‐band, providing a basis for tracking land‐atmosphere interactions. Our study shows that DAV effectively captures cold air masses' origin and seasonal movement. During a cold wave, its phase relationship with air and soil temperatures falls into four categories: precedes (−1.1 to −0.6 days), lags (0.71–0.98 days), in between (−0.62 to 0.34 days), and synchronized. Moreover, DAV lags air temperature in 63% of cases and precedes soil temperature in 59%, consistently fluctuating within their overlap region. This suggests DAV is a more direct indicator of freeze–thaw, reflecting the conditions at the atmosphere–land interface.